Multifunctional Advanced Ceramics for Aeronautical and Aerospace Applications: Study of MgO Al2O3, MgO CaZrO3, and YSZ Ceramic Composites - Shvydyuk, Kateryna Oleksandrivna (2022)
The premise that materials permeate all aspects of our day-a-day lives is well established. The relentless pursuit for increased performance in aeronautical and aerospace industries over the last decades has provided a solid driving force for the study, research, and investigation of advanced ceramics for numerous future investments. The advanced ceramics field is believed to be an enabling technology with the potential to deliver high-value contributions for meeting both future needs and challenges. Moreover, the advanced ceramics industry is quite distinctive due to its high diversity and interdisciplinary nature that encompasses an engaging number of different processing methodologies and a variety of applications. In this sense, this dissertation project focused to perform an extensive and comprehensive literature review research, in addition to further selection, fabrication, testing, and analysis of MgO Al2O3 , MgO CaZrO3 , and YSZ ceramic materials which are intended to satisfy the condition of advanced multifunctional ceramic in the aeronautical and aerospace fields. Within this framework of thought, thermal protection systems, thermal barrier coatings, and dielectric barrier discharge plasma actuator applications were perceived and adopted as a jumping-off point. A step–by–step approach was adopted for the experimental procedure. More precisely, initially, ceramic compositeMgO Al2O3 , MgO CaZrO3 , and YSZ samples were manufactured through a four stages process, i.e., material preparation, processing, sintering, and finishing. After the rectangular plates, bars, and disc specimens were obtained for the three referred compositions, the in-depth study under the microstructural, physical, mechanical, thermal, and electrical characterization followed. Ultimately, many fine ceramics are multifunctional and therefore predestined to solve the forthcoming technological and engineering challenges. It is believed that ceramics offer an enormous potential to be exploited with the knowledge of material science, i.e., through correlations between microstructural, physical, mechanical, thermal, and electrical features.